Proposta de curso semipresencial sobre metodologias ativas para preceptores do ensino em saúde. - Brandão, Fabrizia Reis Pinto (2023)
Introduction: The training of healthcare professionals is an ongoing and challenging process that requires the adoption of effective methodologies for teaching and enhancing future professionals. In this context, active methodologies have stood out as innovative approaches that promote active student participation, the development of practical skills, and the construction of meaningful knowledge. Preceptors play a fundamental role in student training, justifying the provision of support and guidance to these professionals. Objective: to propose a blended course on active teaching methodologies for healthcare preceptors. Methodology: the development of the course proposal was carried out in two stages. The first part consisted of a scoping review to map active methodologies for real-world healthcare education scenarios. In the second stage, the researchers constructed a hybrid course proposal based on the methodologies found in the scoping review, using the methodological framework of the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) to structure this proposal. Results and discussion: The scoping review evidenced eight different types of active methodologies in the selected studies, which composed the course proposal. The following topics were addressed through three theoretical-practical modules: 1) Real practice scenario in healthcare education. 2) Active learning methodologies for real-world healthcare education scenarios; 3) Planning active teaching methodologies in healthcare for real-world scenarios according to learning objectives; 4) Strategies for healthcare teaching practice in the real world setting. Thus, a blended course was proposed for healthcare preceptors, based on the theoretical framework of the scoping review. Conclusion: The proposal for the blended course allowed the strengthening of pedagogical skills for preceptors, enabling them to effectively apply active methodologies in the context of healthcare practice. Therefore, this training can contribute to improving the quality of healthcare student education.